Formulasi Krim yang Mengandung Ekstrak Biji Kopi Robusta (Coffea canephora L.) dan Tantangannya dalam Menghambat Staphylococcus aureus: Studi Potensi Terapi Luka pada Penderita Diabetes - Andari, Putri; Sembiring, Novitaria Br; Ginting, Astriani Natalia Br (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Diabetes mellitus is a chronic metabolic disorder that can cause wounds that are difficult to heal and susceptible to bacterial infection, especially Staphylococcus aureus. This study aims to formulate an antibacterial cream preparation containing robust coffee bean extract (Coffea canephora L.) and evaluate its activity against Staphylococcus aureus. The extract was obtained through maceration with 96% ethanol with a crude yield of 30% and an extract yield of 14.05%. Phytochemical screening showed the presence of alkaloids, flavonoids, tannins, phenols, saponins, and terpenoids. Antibacterial testing of the extract showed inhibitory activity against Staphylococcus aureus at concentrations of 30% (7.73–8.44 mm) and 50% (8.52–13.16 mm). The extract was then formulated into creams with varying concentrations of 0%, 30%, and 50%. All formulations met the physical parameters, except for the cream that did not contain the extract, which showed a pH higher than the ideal range for topical application and showed a decrease in spreadability with increasing extract concentration. However, testing the antibacterial activity of the cream preparations using the disk diffusion method did not produce an inhibition zone in any of the formulations tested. The results of this study indicate that although Robusta coffee bean extract shows activity in vitro, it has not been successfully applied in cream formulations with the existing bases and testing methods. These findings highlight the major challenges in developing natural topical preparations, particularly regarding the selection of formulation bases and appropriate evaluation methods for semisolid preparations.